“Danzas de la diáspora: intérpretes valientes” (Traducción) - Amigo, Ricardo (Interseções: Revista de Estudos Interdisciplinares, 2022)
Traducción del texto de Yvonne Daniel. From Caribbean and Atlantic Diaspora Dance: Igniting Citizenship. Copyright 2011 by the Board of Trustees of the University of Illinois. Used with permission of the University of Illinois Press.